Humanistic Counseling Psychology Review of Deviant Gigolo Behavior - Dody Riswanto; Adaobi Jennifer Iloakasia (International Journal of Counseling and Psychotherapy, 2025)
Objective: This study aims to review the mental and psychological conditions of men who work as gigolos based on the perspective of Rogers' humanistic counseling psychology theory. Method: This study uses a qualitative descriptive approach. Data collection techniques are interviews, observations, documentation studies, and audio-visual information. Data analysis is carried out by concluding to produce meaning. Results: The main factor that motivates gigolo men is economic factors. Sexual transactions with women generate money and other materials, such as giving gifts of mobile phones (cell phones), laptops, clothes, food, housing, and other goods. Gigolo men use Facebook social media to promote themselves to women. Conclusion: The solution to Rogers' humanistic counseling psychology problems regarding gigolo behavioral deviations is as follows: 1) respondents must build self-confidence to quit the gigolo profession; 2) respondents must be honest and more open about the experiences they have experienced; 3) respondents must have the responsibility to solve their problems; 4) respondents must eliminate erroneous perceptions such as fear of being poor and others; 5) Respondents must be able to accept themselves to express feelings of anger, hatred, shame, anxiety, fear, and others that the respondents initially avoided. Contribution: This research contributes to developing guidance and counseling science, especially in developing humanistic counseling psychology theory.